Strain attribution of Ukrainian isolates of Zucchini yellow mosaic virus and their occurrence in Ukraine - Tsvigun, V.O.; Rudneva, T.O.; Shevchenko, T.P.; Budzanivska, I.G.; Polishchuk, V.P. (Вiopolymers and Cell, 2016)
Aim. Establishing the strain attribution of Ukrainian isolates of Zucchini yellow mosaic virus ZYMV and their occurrence in Ukraine. Methods. Visual examination, DAS-ELISA, RT-PCR, DNA sequencing, and phylogenetic analysis. Results. Plants from Cucurbitaceae family were checked for the presence of ZYMV antigens. DAS-ELISA showed that 41 % of examined cucurbit plants were infected by ZYMV. The infected plants were detected in agroecosystems of Vinnytsia, Zaporizhzhia, Kyiv, Poltava and Cherkasy regions. cDNA of 605 bp corresponding to the Nib/CP genome region of ZYMV was obtained using RT-PCR. Phylogenetic analysis of the nucleotide sequence of the Nib/CP region of Ukrainian isolates was conducted. Conclusions. The identification of infected plants in 5 of 9 inspected agroecosystems suggests a high prevalence of the ZYMV infection in Ukraine. The topology of a reconstructed phylogenetic tree confirmed the previously established clustering of ZYMV isolates into three groups. The phylogenetic positioning of the Ukrainian ZYMV isolates on this tree demonstrates that they belong to a subgroup I of group A. This group is the most numerous group, which consists of members of different geographic origins. The ZYMV isolates circulating in Ukraine were found to be nearly identical: their levels of pairwise identity range from 99.7 to100. They have a monophyletic origin with the European isolates from Austria (AJ420017), Slovenia (AJ420018), Serbia (HM072432), Hungary (AJ459955), Slovakia (DQ124239). The levels of pairwise identity between the Ukrainian and European isolates range from 94.3 to 100 %. Мета. Встановити штамову приналежність українських ізолятів вірусу жовтої мозаїки цукіні та дослідити їх поширення на території України. Методи. У роботі були використані наступні методи: візуальна діагностика, імуноферментний аналіз, ЗТ-ПЛР, сиквенування та філогенетичний аналіз. Результати. Перевірено рослини родини Cucurbitaceae на наявність антигенів вірусу жовтої мозаїки цукіні (ВЖМЦ). Встановлено, що 41 % перевірених рослин родини Cucurbitaceae уражені вірусом жовтої мозаїки цукіні. Вірусінфіковані рослини були наявні в агроценозах Вінницької, Запорізької, Київської, Полтавської та Черкаської областей. У результаті проведення ЗТ–ПЛР було отримано продукти ампліфікації розміром 605 п.о., що відповідає за розміром ділянці геному, яка кодує Nib/CP вірусу жовтої мозаїки цукіні. За результатами даних сиквенсу побудувано філогенетичне дерево виділених ізолятів ZYMV. Висновки. Ідентифікація інфікованих рослин у 5 із 9 обстежуваних агроценозів показала широке розповсюдження ZYMV в Україні. Топологія філогенетичного дерева показує, що ізоляти ZYMV формують три групи. Філогенетичне положення на дереві українських ізолятів ZYMV показує їх приналежність до групи А підгрупи 1. Ця група є найбільш чисельною та її представники мають широке географічне поширення. Ізоляти ZYMV, що циркулюють в Україні, виявилися близькоспоріднені між собою. Відсоток ідентичності між ними знаходиться в діапазоні від 99,7 до 100. Дані ізоляти ZYMV мають спільне походження з європейськими ізолятами з Австрії (AJ420017), Словенії (AJ420018), Сербії (HM072432), Угорщини (AJ459955), Словаччини (DQ124239). Відсоток ідентичності між українськими та європейськими ізолятами знаходиться в межах від 94,3 до 100. Цель. Определить штаммовую принадлежность украинской изолятов вируса желтой мозаики цуккини и исследовать их распространение на территории Украины. Методы. В работе были использованы следующие методы: визуальная диагностика, иммуноферментный анализ, ОТ-ПЦР, сиквенирование и филогенетический анализ. Результаты. Проверены растения семейства Cucurbitaceae на наличие антигенов вируса желтой мозаики цуккини (ВЖМЦ). Установлено, что 41 % проверенных растений семейства Cucurbitaceae поражен вирусом желтой мозаики цуккини. Вирусинфицированные растения имелись в агроценозах Винницкой, Запорожской, Киевской, Полтавской и Черкасской областей. В результате проведения ОТ-ПЦР были получены продукты амплификации размером 605 п.о., что соответствует по размеру участку генома, кодирующему Nib/CP вируса желтой мозаики цуккини. По результатам данных секвенирования построили филогенетическое дерево выделенных изолятов ZYMV. Выводы. Идентификация инфицированных растений в 5 из 9 обследуемых агроценозов показала широкое распространение ZYMV в Украине. Топология филогенетического дерева показывает, что изоляты ZYMV формируют три группы. Филогенетическая позиция на этом дереве изолятов ZYMV показывает их принадлежность к группе А подгруппы 1. Эта группа является наиболее многочисленной и ее представители имеют широкое географическое распространение. Данные изоляты ZYMV оказались близкородственными между собой. Процент идентичности между ними находился в диапазоне от 99,7 до 100. Изоляты ZYMV, циркулирующие в Украине, имеют общее происхождение с европейскими изолятами из Австрии (AJ420017), Словении (AJ420018), Сербии (HM072432), Венгрии (AJ459955), Словакии (DQ124239). Процент идентичности между украинскими и европейскими изолятами находится в пределах от 94,3 до 100.